The Clinical Applications of Serum and Urinary Biomarkers in Prostate Cancer - Renu Eapen, Peter Lonergan, Dominic Bagguley, Sean Ong, Ben Condon, Nathan Lawrentschuck, Maxwell Meng (Société Internationale d’Urologie Journal)
At every stage of the prostate cancer journey from screening and diagnosis to management of advanced disease, patients and clinicians face dilemmas and decisions that can impact long-term outcomes. Although traditional risk stratification in prostate cancer is based on serum prostate specific antigen, clinical stage and Gleason score, in recent years, biomarkers have been developed that may be useful in several clinical scenarios. Biomarkers that can accurately predict an individual patient’s risk, prognosis, and response to specific treatments could lead to improvements in decision-making and clinical care. Although there is evidence to support the use of biomarkers to guide management decisions, the optimal scenario in which to use them, how to interpret the results, and how to incorporate those results into clinical decision-making can be confusing. Nevertheless, in the era of personalized and precision medicine, it is important for clinicians to be aware of what tests are available, what clinical questions they seek to answer, and what limitations they have. This review focuses on the serum and urine biomarkers for the management of prostate cancer that have been under intense investigation in recent years.